Minoritetspolitisk historie som profesjonskunnskap – en personlig refleksjon om «praktisk relevans»: English title: The history of minorities as professional knowledge – a personal reflection on "practical relevance" - Christensen, Cato (FLEKS - Scandinavian Journal of Intercultural Theory and Practice, 2019)
Working at Oslo Metropolitan University, which aspire to be a “university for professional education”, I often sense an expectation that my teaching should have “practical relevance” for the students. But does it need to, always?